Jurisdiction and competence: doctrinal outlines (Revista do Tribunal Regional Federal da 3ª Região, 2013)
This modest study aims to outline some fundamental elements of the concept of jurisdiction and competence, in addition to establishing the main nuances that led to the historical evolution of the very meaning of jurisdiction throughout the liberal and contemporary states, as a reflection of the development of world constitutionalism. Thus, the article has been systematized into topics: first (I), the notion of jurisdiction has been delimited since its emergence, in the light of the principles and values of the liberal state, then (II), the influences that contemporary neoconstitutionalism has brought to it are exposed and, finally (III), the concept of jurisdiction is established, with its main classifications. Far from claiming to have exhausted the subject, which is of immeasurable vastness and the object of study of various sciences (legal, philosophical, sociological and political), this article will offer the reader a general overview of the doctrinal concepts of jurisdiction and competence, addressing the main aspects related to them and which are explicitly or implicitly present in the daily life of the legal operator.
Keywords: jurisdiction; competence; historical evolution; constitutionalism